The impact of the unfair commercial practices directive (2005/29/EC) on contract law - Đurović, Mateja (European University Institute, 2014)
This thesis examines the relationship between the law on unfair commercial practices and consumer contract law. The thesis develops the claim that Directive 2005/29/EC, on unfair commercial practices (UCPD) has had a strong impact on the content of consumer contract law, despite the declaration concerning the independence between both branches of law contained in Article 3(2) UCPD. In order to substantiate this claim, the thesis examines the implications for consumer contract law of the main components of the regulatory regime laid down by the UCPD, namely, (1) the notion of average consumer, (2) the duty to trade fairly, (3) the duty of information and (4) the remedies. By looking both at the theoretical underpinnings and at the actual operation of this regulatory regime, the thesis casts light on the way in which the UCPD has shaped consumer contract law. The thesis further shows that this is an ongoing phenomenon whose ramifications may be far-reaching, for it implies that the UCPD is powerfully fuelling the Europeanization of contract law.
Keywords: Consumer protection; Contracts; European Union countries

The action for injunction in EU consumer law - Ogorzałek, Magdalena (European University Institute, 2014)
In 1998 the European Union adopted a new self-standing instrument of collective enforcement - the Action for Injunction. Until then, the main focus was on the improvement of the position of the individual consumer through the adoption of substantive consumer law directives. The Injunction Directive provides for a general framework on consumer law enforcement in national and cross-border litigation. Qualified entities, public agencies and/or consumer organisations, are granted legal standing. National courts are bound to mutually respect the standing of EU wide registered qualified entities. Outside these clear-cut rules on the mutual recognition of standing, the Injunction Directive remains largely silent. The implementation into 28 Member States swiftly revealed the rather limited harmonising effect. The thesis investigates and explains how despite the legally approved diversity, the Injunction Directive contains the potential to turn diversity into convergence. The key to understanding the potential is the thesis of dualism of enforcement measures. Read together with the Annex the Injunction Directive establishes the deep interconnection between collective and individual enforcement, of substantive and procedural enforcement, of judicial and administrative enforcement. The different levels and means of enforcement should not be regarded separately but should always be looked at in their interplay, in their mutual institutional design and their mutual impact. Evidence for convergence can be found in the Invitel judgment of the ECJ and in the practice of consumer organisations via co-ordination actions across borders by which they overcome the boundaries of collective vs. individual or judicial vs. administrative enforcement. Regulation 2006/2004 re-adjusts the dualistic structure of enforcement in favour of public bodies and promotes convergence through para-legal means, through new modes of enforcement, through co-operation and co-ordination outside courts and in open interaction between administrative bodies, to which consumer organisations are admitted on approval only.
Keywords: Consumer protection; European Union countries; Injunctions